The printmaker's art : a guide to the processes used by artists from the Renaissance to the present day - Brocklehurst, Hannah; Watson, Kerry (Librarian); National Galleries of Scotland ([Edinburgh] : National Galleries of Scotland, 2015)
The print collections of the National Galleries of Scotland reveal a diverse and dazzling variety of different techniques and approaches to printmaking. From exquisite copperplate engravings by the old masters to woodblocks cut on kitchen tables, this book examines key works by artists from Durer to Warhol and beyond, giving readers an introduction to printmaking as an art form and an understanding of the different working methods and materials. Through technical summaries and featured examples, 'The printmaker's art' draws on the print and archive collections to illustrate and explain the mysteries of printmaking.
Foreword --Introduction --One: Relief Processes: Woodcut - Chiascuro woodcut and colour woodcut - Linocut - Wood engraving --Two: Intaglio Processes: Engraving - Mezzotint - Etching - Aquatint and drypoint - Blind printing (embossing and debossing) --Three: Planographic Processes: Lithography - Monotype --Four: Screenprinting and Stencilling Processes: Screenprinting - Stencilling --Five: Photomechanical and Digital Processes: Photogravure and collotype - Inkjet Printing --Further examples in the collection - Glossary of printmaking terms.
Includes bibliographical references.
Keywords: Prints -- History; Prints -- Technique -- History; Mezzotint engraving; Aquatint; Lithography; Ink-jet printing